THE THRILLER FORMULA OF PLOT IN DON’T BREATHE FILM BY FEDE ALVAREZ - rizka salsabila; hasbi assidiqi (Universitas Islam Negeri Sunan Gunung Djati, 2019)
This research is about Thriller Formula of Plot in Don’t Breathe film by Fede Alvarez. The objectives of this research is to describe how is the thriller formula explain through plot in Don’t Breathe film. The method use in this research is structuralism method. Then, the object and the source of data in the film Don’t Breathe by Fede Alvarez, which was published in 2009 and the duration consists of 1 hour 28 minutes. Based on the findings and discussion, the writer concluded thriller formula can be seen through plot. In this research, the researcher finds thriller formula through plot consisting of complicated stories, frequent plot twist, violence, emphasis story on action and conflict, the protagonist triumphs over evil and survive and suspense. The result of the analysis shows that there are 40 data of plot. The implication of this research is to give understanding to the readers especially focused on the thriller in order to improve the ability of learners and readers in understanding literature. Expectantly, this research can give many benefits for the readers and all of students of English Literature to learn more about thriller.Key words: Don’t Breathe, thriller, thriller formula in plot.